Analysis of qualitative data : vol 2 new developments - Haberman, Shelby J. (New York : Academic Press, 1979)
The two volumes discuss a variety of models of qualitative data analysis.
Includes bibliographical references: v. 1, p. 354-359; v. 2, p. 597-601 and indexes.
oif 08/02/2019
Loans
Keywords: Log-linear models; Contingency tables; Social sciences---Statistical methods